Effect of Organic Foliar Application on Seed Yield and Quality in Senna (Cassia angustifolia) - V. RAMASAMY; A. VIJAYAKUMAR (Seed Research, 2026)
An experiment was carried out with foliar application of organics viz. Panchagavya (2% & 4%), humic acid (0.2% & 0.4%), moringa leaf extract (2% & 4%) and in combinations at vegetative, flowering and pod filling stage to improve plant growth and seed yield in Senna. The result revealed that, the 4 per cent Panchgavya foliar spray induced earlier 50 per cent flowering (52.7 days), number of pods (53.0 plant), shelling percentage (61.6%) and pod yield (12.823 g plant¹) resulting in maximum seed yield (7.902 g/plant). The highest 100 seed weight (2.543 g), seedling root length (11.84 cm), shoot length, (8.33 cm), dry matter production (107.3 mg seedlings"), vigour index (1869) and alpha amylase activity (12.1 mm) were registered by the resultant seed from 0.2 per cent humic acid foliar application. The result revealed that foliar application of 4 per cent Panchagavya (or) 0.2 per cent humic acid significantly increased the growth and yield and the resultant seed quality parameters.